Synthesis, ADME Evaluation, and In Vitro Antimycobacterial Studies of a Novel Series of 2-Thiazolylimino-5-Arylidene-4-Thiazolidinone Derivatives - Mital, Alka; Prasad Burman, Rohani; Gour, Rajesh; Singh Jhamb, Sarbjit; Singh Gill, Manjinder (Anti-Infective Agents, 2017)
Background: The emergence of multi-drug resistant and extensively drug-resistant cases of tuberculosis has lead to the search for new structural classes of anti-tuberculosis drugs. There are many reports on antimycobacterial screening of compounds containing the 4-thiazolidinone moiety. The 5- arylidene moiety in the 2-heteroarylimino-5-benzylidene-4-thiazolidinone scaffold plays an important role in antimicrobial activity against Gram-positive and Gram-negative bacteria, yeasts and moulds. Objective: To synthesize 2-thiazolylimino-5-arylidene-4-thiazolidinone derivatives, with different substituents on the aryl ring, and evaluate their in vitro antimycobacterial activity against M. tb H37Rv. Methods: The derivatives were synthesized by previously reported methods, and structures confirmed by spectral data. Qikprop, the ADME prediction program was used in predicting pharmacokinetic properties of the derivatives, which helped in designing and synthesis of novel and more potent analogs. In vitro antimycobacterial activity against drug-sensitive M. tb H37Rv was performed in BACTEC-460 TB radiometric system. Results: The synthesis and antimycobacterial activities of 2-thiazolylimino-5-arylidene-4-thiazolidinone derivatives have been reported. The chemical modifications not only altered the physicochemical properties but also pharmacological activities. The compounds exhibited moderate to excellent in vitro activity (88-99.7% inhibition) against M. tb H37Rv, and few demonstrated >99% inhibition at 6.25 μg/mL. The activity was considerably affected by various substituents and compounds with di- and trisubstitutions on the aromatic ring of the 4-thiazolidinone were more active. Conclusion: These preliminary but encouraging results indicate that 2-thiazolylimino-5-arylidene-4-thiazolidinones are promising scaffolds for design and development of new molecules for antimycobacterial activity. Several compounds were identified as novel and potential lead for design and synthesis of new antimycobacterial agents.
Keywords: Antimycobacterial activity